If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x=2(2x-3)
We simplify the equation to the form, which is simple to understand
3x=2(2x-3)
Reorder the terms in parentheses
3x=+(+4x-6)
Remove unnecessary parentheses
+3x=+4x-6
We move all terms containing x to the left and all other terms to the right.
+3x-4x=-6
We simplify left and right side of the equation.
-1x=-6
We divide both sides of the equation by -1 to get x.
x=6
| k/2+5=8 | | s-32=-48 | | v+(v-30.8)+(v+27.3)=202.9 | | 3x^3-7x^2+6x-2=0 | | y^2+2x+8y+13=0 | | 12x^2-24-9=0 | | -7/9x23/4 | | x+(x+6)=382 | | x=-9/2-5/3 | | 4.2/-0.15 | | x-7.7=-3.5 | | -9/2-5/3 | | -11x^2+20x=0 | | 3x^3-7x^2=2-6x | | -27/12/-1/6 | | x-50=32 | | 25m^2-9/16 | | r+27=14 | | X-9=10/10(11-7x) | | x+30.8+x+27.3=202.9 | | -1/6(x-18)+1/2(x+2)=-4 | | 2/7x+4=16/7x | | 12(t-3)+3t=5(3t+4)-9 | | -5/7+2/3 | | 6x^2+20=0 | | 8p-21=-35+6p | | -2/3+1/2 | | 6p-17=-18+7p | | 15-.5P=.25P | | 4+2/7=16/7x | | x^2+20x+4=0 | | -11/4x-31/6 |